School and Family Partnerships: Contribution of Transformational Teachers in Implementing the Autonomous Learning Curriculum Educational Institutions in Bone, Indonesia - Syarifuddin, Samsinar; Tahir, Andi; Fatimah, Fatimah; Abidin, Kurniati; Syarifuddin, Fitriyawany (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study seeks to investigate the collaboration between schools and families, with a specific focus on the role of transformational teachers in promoting autonomous learning at educational institutions in Bone, South Sulawesi. The interaction between schools and families is undeniably crucial in the development of the three education centers in Indonesia. The study is conducted using a mixed-methods approach, which are examined through the lens of Islamic education philosophy employing a concurrent triangulation strategy model or design. The data were collected through interview, observation, document analysis, and questionnaires. The findings of this study suggest that elementary school teachers in Tanete Riattang Barat District, Bone Regency, have effectively fulfilled their duty as facilitators of learning, and the implementation of the autonomous learning curriculum has been successful. The transformational teacher variable and the implementation variable of the Autonomous Learning Curriculum have a correlation coefficient of 0.75, indicating a strong positive link. The transformational teachers (X) contribute 56.3% to the implementation of the independent learning curriculum (Y) and have a strong impact on the relationship between transformationanl teachers and the implementation of the independent learning curriculum. The collaboration between families and schools, particularly between parents and teachers, has been established through effective communication, since it enhances the educational experience, both within the school environment and at home. In the realm of Islamic Education, both the home and school play a crucial role in shaping the character of children, enabling them to develop into exceptional, self-reliant, patriotic, innovative, and discerning individuals.